Świat (nie)kontrolowanych emocji. O literaturoterapii Victorii Reicher - Lenart, Agnieszka (Studia Rossica Posnaniensia, 2023)
The article deals with the therapeutic aspects of literature. The research material is the prose of Victoria Reicher, a writer who represents the younger generation of Russian-Israeli olim. The author analyses selected works from Yoshka’s house and Telling tales to the left collections. In the texts analyzed, the author sees specific patterns of behavior, typical not only of Russian-speaking repatriates in Israel but also describing the contemporary human, immersed in the chaos of this world. One of the characteristics of Reicher’s prose is carnivalization. The humor and chaos reveal a frank and true picture of everyday life. According to the author, Reicher’s literature has a purifying purpose and contains psychodrama elements. It provokes reflection, stimulates mental and emotional activity, and soothes negative emotions. The author proves that Reicher, a writer, and trained psychologist, can help readers solve their problems – through her texts, blog, and constant presence on the Internet. Reicher’s literature has the characteristics of therapeutic literature. Moreover, it is an affective bibliotherapy, and guided reading.